1995
DOI: 10.1055/s-2007-1013763
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Porcine Biological Valves with Pericardial Valves - a 12-Year Clinical Experience with 1123 Bio-Prostheses

Abstract: In order to evaluate selective differences of biological porcine valves versus pericardial valves and to analyze various valve models, 8 different bioprostheses (4 porcine valves, 4 pericardial valves) were studied in a 12-year follow-up. From 1978 to 1990, 476 porcine bioprostheses (Carpentier-Edwards: n = 104, Carpentier Edwards Supraanular: n = 59, Hancock I: n = 41, Hancock II: n = 272) and 647 pericardial valves (Hancock-Extracorporeal: n = 479, Ionescu-Shiley: n = 76, Carpentier-Edwards: n = 57, Mitroflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…During the last 15 years stented biological aortic valve substitutes have been investigated in an astounding number of publications [1][2][3][6][7][8]. It was shown that both types of biological valves demonstrate reasonable hemodynamic performance in the clinical setting [1][2][3]6].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…During the last 15 years stented biological aortic valve substitutes have been investigated in an astounding number of publications [1][2][3][6][7][8]. It was shown that both types of biological valves demonstrate reasonable hemodynamic performance in the clinical setting [1][2][3]6].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that both types of biological valves demonstrate reasonable hemodynamic performance in the clinical setting [1][2][3]6]. It was also shown that the observed differences in transvalvular gradients were not followed by significant differences in left ventricular remodelling as well as clinical outcome [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations